Pengembangan Media Pembelajaran Fisika Berbasis Multimedia Presentasi (Prezi) Pada Materi Gerak Untuk Peserta Didik Kelas VIII MTsN Koto Baru Solok - Hurriyah, Hurriyah (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2017)
Physics is one branch of Natural Sciences (IPA) that underlies the development of science and technology. The main purpose of studying physics is to understand the natural phenomena of seeking natural knowledge (law) (Trustho, 2008: 5). Natural Science (IPA) and technology are two things that are related to each other. This study aims to: 1) Produce a multimedia-based physics learning media presentation (prezi) valid, practical, and effective. This research is a development research using research and development (R&D) method developed by Borg and Gall. The result of data analysis obtained the validation value of multimedia prezi 86.5 category is very valid. The value of prehearsal multimedia practice by IPA educators 86.6 categories is very practical. The value of practicality by learners for small-scale test 81.1 and large-scale test 88.2 categories is very practical. The effectiveness test obtained results 88.4 categories are very effective. This shows that multimedia-based physics-based teaching media (prezi) can be used as a medium of learning in SMP / MTs.